2018
DOI: 10.25066/agrotec.v39i3.40383
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de animais com anticorpos anti-Leptospira spp. na região de Uberlândia, MG, 2011-2014

Abstract: A Leptospirose é uma doença cosmopolita de grande relevância para a Medicina Veterinária por ocorrer em diversas espécies domesticas e silvestres, podendo causar prejuízos nos setores produtivos e preocupações para a saúde pública. Assim, o objetivo do trabalho foi avaliar a frequência de bovinos, bubalinos, caninos selvagens, caninos, caprinos, equinos, felinos, ovinos, roedores e suínos sororeagentes ao teste para leptospirose e quais sorogrupos foram mais prevalentes. Para tal, foram compilados os resultado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
2
Order By: Relevance
“…Gurgel-Gonçalves and Cuba (2007) described that the total number of the two species of triatomines, R. neglectus and Psammolestes tertius, captured in bird nests in the palm tree canopy, was similar in different climate seasons. On the other hand, Mendes and Lima (2011) and Meneguetti et al (2012) demonstrated an increase in the number of triatomines captured during rainy season in the municipalities of Uberlandia-MG and Ouro Preto do Oeste-RO, results that differ from what was observed in this study, where rainfall levels did not influence the index of captured species (p> 0.05).…”
Section: Resultscontrasting
confidence: 99%
“…Gurgel-Gonçalves and Cuba (2007) described that the total number of the two species of triatomines, R. neglectus and Psammolestes tertius, captured in bird nests in the palm tree canopy, was similar in different climate seasons. On the other hand, Mendes and Lima (2011) and Meneguetti et al (2012) demonstrated an increase in the number of triatomines captured during rainy season in the municipalities of Uberlandia-MG and Ouro Preto do Oeste-RO, results that differ from what was observed in this study, where rainfall levels did not influence the index of captured species (p> 0.05).…”
Section: Resultscontrasting
confidence: 99%
“…The frequency of leptospirosis in buffaloes in the state of Paraná found in the present study was 77.17% (213/276), a high result close to the 80% (164/205) found by Viana et al (2009) in Pará and 70.58% (216/306) found by Carvalho et al (2015) in Maranhão. The frequency found was higher than those found in other studies conducted in different states of Brazil, such as 28.5% (35/123) in Pernambuco (Oliveira et al 2018), 27.9% (38/136) in Paraíba (Pimenta et al 2019), 67.7% (86/127) in buffaloes in Pará (Silva et al 2009) or 56.25% (18/32) in Minas Gerais (Mendes et al 2018). It is also important to consider that frequency of leptospirosis can be affected by the number of serovars used in MAT testing (Adesiyun et al 2009).…”
Section: Discussioncontrasting
confidence: 72%